Orientasi Nilai Pelaku Musik Hardcore - Sanjaya, Anto; Widjanarko, Mochamad (Jurnal Psikologi: PITUTUR, 2010)
Human  being  is  unique.  No  one  is  either physically  or  psychologically  identical  with others.  Being  different  from  others  requires courage and is the choice in life. Selection of value orientation will make an individual being has a way and control of life as a form of value orientation  which  is  believed  and  embraced. Hardcore  music  performer  is  one  of  many differences  in  value  orientation  adopted  by men. A hardcore music performer certainly has a reason in choosing it as a a way of life.The objective of the research is to know and to  understand  the  value  orientation  of  the hardcore  music  performers  in  the  Kudus Regency. The informants of the reasearch are the  hardcore  music  performers  located  in Kudus Regency who are involved in Komunitas Kudus  Hardcore  Community  (KDHC).  Value orientation in the research is viewed by using motivational types of value which is proposed by  Schwartz.  Orientation  value  proposed  by Schwartz  consists  of  10  types  of  values consisting  of  power,  prestige,  pleasure, stimulation, self direction, unity, virtue, tradition, compatibility and security.Based  on  the  coding  of  interviews  and observations  conducted  on  the  three informants  shows  that  the  hardcore  music performers  in  Kudus  Regency  have  value orientations that lead to the value of creativity and the other value that stands out is the value orientation led to the value of independence.